2017
DOI: 10.1111/mec.14001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of octanoic acid resistance inDrosophila sechellia: functional analysis of a fine‐mapped region

Abstract: Drosophila sechellia is a species of fruit fly endemic to the Seychelles islands. Unlike its generalist sister species, D. sechellia has evolved to be a specialist on the host plant Morinda citrifolia. This specialization is interesting because the plant’s fruit contains secondary defense compounds, primarily octanoic acid (OA), that are lethal to most other Drosophilids. Although ecological and behavioral adaptations to this toxic fruit are known, the genetic basis for evolutionary changes in OA resistance ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 59 publications
(133 reference statements)
4
79
0
Order By: Relevance
“…Because PBO inactivates the function of the MFO system, it is frequently used as a synergist in pesticide formulations. Combination of PBO treatment with exposure to 1.2% OA (concentration determined in previous publication to maximize the ability to see increases and decreases in OA resistance, Andrade Lopez et al ., ) allowed for tests of differences in mortality associated with removal of cytochrome P450 function in the presence of OA. Any observed differences between PBO + OA and OA alone would demonstrate the function of the MFO system in OA resistance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because PBO inactivates the function of the MFO system, it is frequently used as a synergist in pesticide formulations. Combination of PBO treatment with exposure to 1.2% OA (concentration determined in previous publication to maximize the ability to see increases and decreases in OA resistance, Andrade Lopez et al ., ) allowed for tests of differences in mortality associated with removal of cytochrome P450 function in the presence of OA. Any observed differences between PBO + OA and OA alone would demonstrate the function of the MFO system in OA resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Noni fruit produces high levels of medium chain fatty acids including octanoic acid (OA) and hexanoic acid (HA) that represent 58 and 19% of all the volatile compounds produced by M. citrifolia , respectively (Farine et al ., ). Whereas OA and HA are both highly toxic to Drosophila species (Legal et al ., ; Andrade Lopez et al ., ; but see Yassin et al ., ), D. sechellia has evolved resistance to the toxins found in noni fruit.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, a locus on chromosome 3R has been shown to be responsible for the greatest variation in OA resistance between adult D. sechellia and D. simulans and has been narrowed to a 168 kb region containing 18 genes using an introgression based approach (Hungate et al ., ). Utilizing RNA interference in D. melanogaster , this fine‐mapped region was further refined using functional tests of the 18 genes residing in the QTL (Andrade‐Lopez et al ., ). This analysis revealed three genes in the Osiris family, Osiris 6 ( Osi6 ), Osi7 and Osi8 , that led to a decrease in OA resistance when gene expression was ubiquitously knocked down in D. melanogaster (Andrade López et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Utilizing RNA interference in D. melanogaster , this fine‐mapped region was further refined using functional tests of the 18 genes residing in the QTL (Andrade‐Lopez et al ., ). This analysis revealed three genes in the Osiris family, Osiris 6 ( Osi6 ), Osi7 and Osi8 , that led to a decrease in OA resistance when gene expression was ubiquitously knocked down in D. melanogaster (Andrade López et al ., ). A subsequent study revealed knockdown of Osi8 in the larval stage of D. melanogaster also increased susceptibility to OA (Lanno et al ., ).…”
Section: Introductionmentioning
confidence: 97%